Seaweed polysaccharide derived bioaldehyde nanocomposite: Potential application in anticancer therapeutics. (15th July 2020) - Kholiya, Faisal; Chatterjee, Shruti; Bhojani, Gopal; Sen, Subrata; Barkume, Madan; Kasinathan, Nirmal Kumar; Kode, Jyoti; Meena, Ramavatar
Highlights: A one-pot rapid synthesis of bioaldehyde tempted silver nanoparticles in solid form. Gelling seaweed polysaccharide agar-based bioaldehyde to be used for generation of solid Aald –AgNPs. Aald–AgNPs were found to be biocompatible and did not affect growth of normal mesenchymal stem cells. Bioassay results showed anticancer activity in in vitro and in vivo conditions. Easy to handle and store the solid Aald –AgNPs under ambient conditions for use. Abstract: In the present study, we have demonstrated synthesis of agar aldehyde (Aald ) from seaweed polysaccharide and its further successful application for preparation of Aald mediated solid silver nanocomposite (Aald –AgNPs). Aald –AgNPs were characterized for biophysical properties by FTIR, XRD, SEM, TEM, XPS, and UV–vis spectroscopy. Aald –AgNPs were further tested in vitro and in vivo for anticancer activity. The results of the in vitro study revealed that Aald –AgNPs exhibited activity against 3 cancer cell lines. Aald –AgNPs were found to act through causing dose dependent increase in cell size, inducing anueploidy, mitochondrial disintegration and increasing septa formation in cell cytoplasm. Results of in vivo anticancer activity against ME–180, Colon–26, and HL–60 xenograft mice tumor models showed 64 %, 27.3 % and 51 % reduction in tumor volume, respectively with 83–100 % survival rate. Aald –AgNPs exhibited excellent antibacterial activity. It was interesting to note that Aald –AgNPs did not exhibit any significant detrimental effect on viability and metabolic activity of normal bone marrow derived mesenchymal stem cells. This study opens new areas of research for chemists and biologists to use seaweed-derived polymers to develop nanocomposites for cancer therapeutics.